2016
DOI: 10.1111/joor.12445
|View full text |Cite
|
Sign up to set email alerts
|

Non‐carious cervical lesions (NCCLs) in a random sampling community population and the association ofNCCLs with occlusive wear

Abstract: This study investigated the prevalence, risk factors and association of occlusive wear with non-carious cervical lesions (NCCLs) in the general Chinese population. A total of 1320 subjects were recruited, and multistage and random sampling methods of survey spots were performed. All age groups comprised similar numbers of participants and equal numbers of males and females. Each subject completed a structured interview, and all teeth of each subject were examined by a practitioner to determine NCCLs and occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 28 publications
4
45
0
9
Order By: Relevance
“…Eating or drinking acidic foods/beverages more than six times a day was associated with a 2.9 and 2.3 times increase in the likelihood of severe tooth wear in the anterior region and posterior region, respectively. Several factors could contribute to this finding, including the type of diet consumed [23][24][25][26][27], as well as, environmental factors [28] and the method of drinking, such as…”
Section: Discussionmentioning
confidence: 99%
“…Eating or drinking acidic foods/beverages more than six times a day was associated with a 2.9 and 2.3 times increase in the likelihood of severe tooth wear in the anterior region and posterior region, respectively. Several factors could contribute to this finding, including the type of diet consumed [23][24][25][26][27], as well as, environmental factors [28] and the method of drinking, such as…”
Section: Discussionmentioning
confidence: 99%
“…Non-carious cervical lesions (NCCLs) have long been described as highly prevalent [1][2][3][4][5] but their etiological and physiopathological mechanisms remain unclear [2,6]. In advanced stages, they result in functional and aesthetic problems, dentine hypersensitivity and often require extensive restorative work.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Several global studies evaluated the prevalence and degree of tooth wear, which shed light on potential risk factors, such as sociodemographic factors and hygienic habits that contribute to the progression of the condition. [9][10][11][12] In Chengdu city, China, a study about the prevalence of tooth wear in adults showed that 63% suffered from tooth wear: age and intensity of toothbrushing were among the risk factors related to tooth wear. 9 Tooth wear of 97.9% was found in a study conducted in Chile, mainly affecting the anterior teeth, with no differences found between males and females; however, a positive correlation with age was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In Chengdu city, China, a study about the prevalence of tooth wear in adults showed that 63% suffered from tooth wear: age and intensity of toothbrushing were among the risk factors related to tooth wear. 9 Tooth wear of 97.9% was found in a study conducted in Chile, mainly affecting the anterior teeth, with no differences found between males and females; however, a positive correlation with age was observed. 10 In another study in Holland, assessing tooth wear in adults, a prevalence of 80% was observed for moderate tooth wear: greater tooth wear was observed in older individuals, especially males vs females, and in people of lower socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%